1995
DOI: 10.1243/pime_proc_1995_209_307_02
|View full text |Cite
|
Sign up to set email alerts
|

Certification of the Composite Outer Wing of the ATR72

Abstract: The ATR72 was the first civil aircraft with a composite wing, to be certified JAR/FAR 25 (Joint Aviation Requirements/Federal Aviation Regulations). Using the latest developments composites ACJ 25603, AC20-107A comply with the requirements of JAR/FAR 25; the ATR72 composite outer wing box was certified by the DGAC in September 1989 and by FAA in December 1989. This paper deals with Aerospatiale's innovative approach, focusing on four major certification topics: the determination of allowables from statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…Thus, PEEK matrix being much tougher than PPS in tension, possesses fracture toughness 4-8 times greater than that of PPS, as was reported by Vielle et al 1 referring to Tropis et al 15 Three laminates with three stacking sequences were produced in Ten Cate Advanced Composites (TCAC) for different types of tests with each matrix: where N is the number of fabric layers; t the thickness of sample and m f the mass of an unit square of a fabric. The average values and standard deviations of thickness and FVF of the laminates are shown in Table 2.…”
Section: Methodsmentioning
confidence: 64%
“…Thus, PEEK matrix being much tougher than PPS in tension, possesses fracture toughness 4-8 times greater than that of PPS, as was reported by Vielle et al 1 referring to Tropis et al 15 Three laminates with three stacking sequences were produced in Ten Cate Advanced Composites (TCAC) for different types of tests with each matrix: where N is the number of fabric layers; t the thickness of sample and m f the mass of an unit square of a fabric. The average values and standard deviations of thickness and FVF of the laminates are shown in Table 2.…”
Section: Methodsmentioning
confidence: 64%
“…The choice of size is driven by the following compromise: the specimen must be large enough to represent the structural problems and to limit the Saint-Venant's effects while being small enough to keep costs within reasonable limits. In [36], the size of the area of interest was 200 200 mm 2 , which was too small. In the other machines described, the size of the test pieces was of the order of one square meter, which is necessary to represent fuselage sections but is too large and too expensive for a technological test piece.…”
Section: Choice and Description Of The Architecturementioning
confidence: 99%
“…The upper levels of the pyramid involve structural tests on more specific specimens that are more representative of the designs, but always under uniaxial loading. In addition, for composite structures, sizing and damage tolerance methods were developed as part of the certification of the first composite primary structure certified on a civil aircraft, the ATR 72 wing box (Tropis et al [2]) and must also be validated by the pyramid of tests. However, these methods, although they have the advantage of being robust, have the disadvantage of being extremely costly (tens of thousands of tests per aircraft) and generating very long design cycles.…”
Section: State Of the Art And Positioningmentioning
confidence: 99%
“…In the field of aeronautics, it has been demonstrated that a permanent indentation between 0.25 and 0.5 mm is detectable during detailed visual inspection with a probability greater than 99% [12].…”
Section: Permanent Indentation and Damage Tolerance Conceptmentioning
confidence: 99%
“…the dent depth of the impact point, is a crucial aspect for the certification of composite structures with damage tolerance concepts [10][11][12]. Indeed the size of such an indentation determines whether impact damage can be detected or not.…”
Section: Permanent Indentationmentioning
confidence: 99%